PENGARUH EPS, ROI DAN EVA TERHADAP RETURN SAHAM PERUSAHAAN OTOMOTIF DI BEI - Janitra, Putu Vito Veda; Kesuma, I Ketut Wijaya (E-Jurnal Manajemen, 2015)
The purpose of investment done by investors in the capital market is to get return of said investment. Capital gain is a difference between the the stock price now and before. If the stock price is high, so does the return. The kind of informations that can be used to measure the stock return are EPS, ROI, and EVA. The population in this research are all of the automotive company listed in the Bursa Efek Indonesia during 2009-2013 period. Purposive sampling is used to get the sample in this research using criterias and 11 companies are the samples. This research is using multiple linear regression. Earning Per Share and Return On Investment have a significant and positive impact on stock return, meanwhile Economic Value Added do not have a significant impact on stock return.
Keywords: Stock Return, EPS, ROI, EVA